Kerangka Dasar Kurikulum Deep Learning Perspektif Pendidikan Islam dan Arah Kebijakan Menteri Pendidikan Dasar dan Menengah - Andri Irawan; Hanum Salsabila; Liska Amelia; Lulu Nur Lathiifah Jamiilah (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2025)
This article aims to explore the basic framework and mapping of Deep Learning as a curriculum development in the era of the leadership of the Minister of Primary and Secondary Education of the Republic of Indonesia, Abdul Mu'ti. The writing method used by the author is a literature study method by conducting a literature review. This study is a collection of data from several journal articles related to the topic of study. This paper reveals that (1) Deep Learning is an approach that emphasizes the creation of a learning atmosphere and learning process that is conscious, meaningful, and joyful through holistic and integrated thinking, heart, taste, and exercise; (2) Deep Learning in the context of education policy in Indonesia refers to Regulation of the Minister of Primary and Secondary Education of the Republic of Indonesia Number 13 of 2025 concerning Amendments to Regulation of the Minister of Education, Culture, Research, and Technology Number 12 of 2024 concerning the Curriculum for Early Childhood Education, Primary Education, and Secondary Education. Basically, Deep Learning is not a completely new curriculum or what can be considered as the latest curriculum that degrades the previous curriculum. Rather, it is an approach that is already known and has become part of the Merdeka Curriculum; (3) Deep learning is supported by three pillars, namely mindful learning, meaningful learning, and joyful learning; and (4) The implementation of Deep Learning can have a significant positive impact on the quality of education, including improving the quality of learning. Although the concept of Deep Learning sounds promising, its implementation in the field is not without challenges. One of the main challenges is the uneven understanding of this concept among some parties.